High-speed nanoscopic tracking of the position and orientation of a single virus. - Kukura, P; Ewers, H; Müller, C; Renn, A; Helenius, A; Sandoghdar, V (2009)
Optical studies have revealed that, after binding, virions move laterally on the plasma membrane, but the complexity of the cellular environment and the drawbacks of fluorescence microscopy have prevented access to the molecular dynamics of early virus-host couplings, which are important for cell infection. Here we present a colocalization methodology that combines scattering interferometry and single-molecule fluorescence microscopy to visualize both position and orientation of single quantum dot-labeled Simian virus 40 (SV40) particles. By achieving nanometer spatial and 8 ms temporal resolution, we observed sliding and tumbling motions during rapid lateral diffusion on supported lipid bilayers, and repeated back and forth rocking between nanoscopic regions separated by 9 nm. Our findings suggest recurrent swap of receptors and viral pentamers as well as receptor aggregation in nanodomains. We discuss the prospects of our technique for studying virus-membrane interactions and for resolving nanoscopic dynamics of individual biological nano-objects.